Net radiation estimation under pasture and forest in rondônia, Brazil, with TM landsat 5 images - Santos, Carlos Antonio Costa dos; Nascimento, R. L. do; Rao, Tantravahi Venkata Ramana; Manzi, Antônio Ocimar (Atmosfera, 2011)
The main objective of this study is to obtain the spatial distribution of net radiation (RN) in two contrasting vegetation covers (forest and pasture) through the SEBAL algorithm, and to analyze its performance when applied to tropical humid atmospheric conditions. This study was conducted in the state of Rondônia in northwestern Brazil, using four Landsat TM images, as well as, digital elevation model data. The correlation coefficients between estimated (SEBAL) and measured values of RN, and surface albedo are of 0.97 and 0.88, respectively. These results present SEBAL as an important tool to be used in hydrological and environmental studies, and to obtain coherent temporal and spatial variations of surface characteristics, helping in the improvement and validation of model parameterizations. However, the applications of remote sensing techniques in tropical humid climates are difficult, because of the existence of a constant presence of convective clouds.
Keywords: Algorithm; Convective Cloud; Digital Elevation Model; Evapotranspiration; Humid Environment; Landsat Thematic Mapper; Net Radiation; Parameterization; Pasture; Rainforest; Remote Sensing; Satellite Imagery; Spatial Distribution; Spatial Variation; Vegetation Cover; Amazonia; Rondonia